Development of animal feeding additives from mushroom waste media of shochu lees - Fumio Yagi; Yuji Minami; Masayoshi Yamada; Kyohei Kuroda; Masahito Yamauchi (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Mushroom waste medium can be used as a source of enzymes, but few studies on animal feed improvement using it have been found. In this study, the potential as additives for improving feed efficiency was examined. Extracts from waste media containing shochu lees used for growing three mushrooms cultivation: monkey head mushroom (MHM) Hericium erinaceus, oyster mushroom Pleurotus ostreatus, and shiitake mushroom Lentinula edodes were investigated. Methods Several polysaccharide hydrolase activities in the extracts were measured and the following feedstuffs were partially digested by the extracts: Italian ryegrass, rice straw, and sweet potato runner. Digestibility of neutral detergent fiber (NDF) in the three feedstuffs was compared by the analysis of sugar composition of residual NDF after hydrolysis with sulfuric acid and trifluoroacetic acid. Antioxidant activity of the extract from waste media was also determined by DPPH radical method. Results The polysaccharide hydrolase activity differed depending on the kind of mushroom and waste medium composition. The waste media containing sweet potato shochu lees showed higher enzyme activities than the standard media did. The additives reduced NDF content in the feedstuffs, especially in treating sweet potato runner with MHM extract. MHM remarkably decreased xylose in NDF of rice straw, and glucose and xylose in NDF of sweet potato runner. Conclusions The results suggested that the additives might be effective in improving the efficiency of the feedstuffs for heat-stressed or weakened livestock.